Whole-Genome Sequencing of Burkholderia pseudomallei Isolates from an Unusual Melioidosis Case Identifies a Polyclonal Infection with the Same Multilocus Sequence Type - Price, Erin P. (J Clin Microbiol, 2014)
Twelve Burkholderia pseudomallei isolates collected over a 32-month period from a patient with chronic melioidosis demonstrated identical multilocus sequence types (STs). However, whole-genome sequencing suggests a polyclonal infection. This study is the first to report a mixed infection with the same ST.